O mulato de Aluísio Azevedo e o diálogo com crônicas jornalísticas: afinidades e rupturas com o legado naturalista - Silva, Luciana Uhren Meira (2012)
The aim of this research is appraise to what extent the dialogue between journalistic chronicle and novel labeled the naturalist conception of Aluísio Azevedo s first naturalism novel, O Mulato, published in 1881. The chronicles were previously produced, while and after the romance had been released, they have strong elements that launch basis from Aluísio related to naturalism matters. Besides, they were presented as propaganda, about the romance itself, the author and his readers. At this point the issue key of this research is marked, i. e. to what extent the naturalistic theses -- real sense linked to personal expression are shown in novelist-chronicler s speech. To respond this matter, hypothesis that states the procedure difference in the way how chronicle and novel are present in the naturalism context: in chronicle, personal expression is reduced when it faces the involvement taking into consideration criticism as well as social reality, in novel this scenario is inverted and personal expression is promoted to literary status by means of thoughts that dare the power of poetics descriptions. Mikhail Bakhtin and Wayne Booth give theoretical basis and studies about the development of novelistic speech, besides Zola s novel principles and his rupture between theory and writing practical. Findings coming from the research assured us the differences between chronicle and novel considering Zola s naturalistic principle. It makes clear, in the chronicle speech, the denounce and social criticism by means of ironic and the way he declares them, many times in distorted figure; in novel, it is the impressionist speech that assumes the rupture, it could be wanted by objectiveness, or by personal expression, revealing, more than rhetorical pleasure , the ethic commitment with the writer s duty that is, exactly, in his literary-language s conscience